PENENTUAN AREA PRIORITAS PENANGANAN PASCA BANJIR BERBASIS ANALISIS SPASIAL DI KECAMATAN KARANG INTAN - Muhammad Angga Prabowo; Wahyu Wahyu; Muhammad Husaini; Badaruddin Badaruddin (EnviroScienteae, 2023)
The mining and plantation sector has a vital role in increasing GRDP and provides a positive multiplier effect on output, added value, income, and labor. However, on the other hand, it also has a negative impact on increasing environmental damage and climate change, resulting in flood disasters in almost all areas of South Kalimantan. Disaster mitigation planning is the main key to disaster management. This research compiles a post-flood management plan, especially in Karang Intan Sub-district. This research is quantitative research. The method used is a spatial analysis by overlaying the flood water level with objects in it such as houses, roads, and people. Objects that are vulnerable to flooding are those located at flood water levels above class 2 (TMA=0.1-0.5 meters). The number of houses that are vulnerable to being affected is 2,107 units, consisting of 697 units of safe flood conditions, 170 units of safe enough, and 1,239 units of vulnerable. Based on this, the evacuation point was determined as many as 23 points with the most evacuation point coverage, namely evacuation point number 22, which can reach 340 houses in Sungai Alang Village.